answersLogoWhite

0


Best Answer

4p+7q

User Avatar

Wiki User

โˆ™ 2011-06-05 17:53:10
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards

J's study guide

2 cards

What is the name of Steve on minecraft's name

What is love

โžก๏ธ
See all cards

Steel Tip Darts Out Chart

96 cards

170

169

168

167

โžก๏ธ
See all cards

Add your answer:

Earn +20 pts
Q: What is p plus 3p plus 2q plus 5q?
Write your answer...
Submit
Related questions

What is the answer to 4p plus 2q-3p-2q?

simply add the like terms: 4p -3p +2q -2q = p


What is 4q 5r 7p 7r 2q 3p?

It is a string of algebraic terms.


How do you factor 4p plus 10q?

2(2p + 5q)


What expression is equivalent to 10q plus 25r?

5*(2q + 5r)


What is the perpendicular bisector equation of the line segment of p q and 7p 3q?

In its general form it works out as: 3px+qy-12p2-2q2 = 0Improved Answer:-Points:(p, q) and (7p, 3q)Slope: q/3pPerpendicular slope: -3p/qMidpoint: (4p, 2q)Equation: y-2q = -3p/q(x-4p) => yq = -3px+12p2+2q2Perpendicular bisector equation in its general form: 3px+qy-12x2-2q2 = 0


What is the answer to this question 7p plus 2q equals 46 and 5p plus 3q equals 36?

7p + 2q = 46 . . . . (A) 5p + 3q = 36 . . . . (B) 3*(A): 21p + 6q = 138 2*(B): 10p + 6q = 72 Subtracting gives 11p = 66 so that p = 6 Substitute for p in (A): 7*6 + 2q = 46 or 42 + 2q = 46 which gives 2q = 4 so that q = 2 Solution: (p, q) = (6,2)


How do you factorise this 6p plus 12q plus 18r?

6p + 12q + 18r = 6 (p + 2q + 3r)


What is 4p -p- p- p plus 2p?

6


What is p plus q and 2p?

It is an expression that can be simplified to: 3p+q


What is the first and second derivative of R equals q2 plus 3qa plus a2?

Rprime= 2q + 2a + 3 Rdoubleprime= 4


What is negative 27 equals negative 3p plus 15 3p?

Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "equals", "squared". There is no symbol between 15 and 3p.


What must be added to 3p plus 9 to give 7-p?

p=-1


What is the difference between additional skill identifier F7 and 5Q?

They are both Pathfinder. F7 is Enlisted, 5Q is officer.


What is 10p 2 3p equals 36?

It is an equation with the plus or minus signs missing which makes it impossible to solve.


What are the factors of q 3-q 2 2q-2?

The question is incomplete in the sense that there is no +/- sign between q2 and 2q. Considering plus '+' sign. q3 - q2 + 2q - 2 q2(q - 1) + 2(q - 1) (q2 + 2)(q - 1) Considering minus '-' sign. q3 - q2 - 2q - 2 The expression can't be factored. However if we consider the question complete then it is written as: q3 - q2(2q) - 2 q3 - 2q3 - 2 -q3 - 2 -(q + 21/3)(q2 - 21/3 + 22/3)


Simplify p squared minus 3p over p squared minus 6p plus 9 divided by 20 over 4p-12?

answer is p/5. problem: {[(p^2)-3p]/[(p^2)-6p+9]}/{20/(4p-12)}


What is the product 2 of q?

2q


Solve this inequality 3p - 6 21?

3p - 6 > 21 3p - 6+6 > 21+6 3p > 27 3p/3 > 27/3 p>9 this WILL help


What is p and q when 2p add 4q is 16 and 7p add 12q is 52?

2p+4q=16 (now divide the equation by two) p+2q=8 (now subtract 2q) p=8-2q 7p+12q=52 (substitue the answer you got for p in the previous equation) 7(8-2q)+12q=52 (multiply the first equation by 7) 56-14q+12q=52 (subtract 14q from 12q) 56-2q=52 (subtract the 56 from 52) -2q=-4 (multiply by -1) 2q=4 (divide by 2) q=2 p=8-2q (substitute the value of q) p=8-2(2) (multiply) p=8-4 (subtract) p=4 2p+4q=16 (check your answers with the new values of p and q) 2(4)+4(2)=16 8+8=16 true 7p+12q=52 7(4)+12(2)=52 28+24=52 true


What is 2q ic?

2 quarts ice cream


How do you simplify 3p by the power of 3 X 3p by the power of 3 by the power of 2?

3p9


6p-2-3p equals 16?

If: 6p-2-3p = 16 Then: p = 6


What element from the periodic table has 3p- for an electron configuration?

Al, Si, P, S, Cl and Ar have 1, 2, 3, 4, 5 and 6 electrons respectively in the 3p (valence orbitals). However all elements after Argon have completely filled 3p orbitals though 3p is not the valence orbital.


What is -3p 6p?

9


How do you find the factor of p2 plus 3p-4?

p2 + 3p - 4What two factors of - 4 add up to 3 ??(p - 1)(p + 4)===============so,p = 1p = - 4

People also asked

If p and q are positive integers and 1 plus p plus q plus pq 14 what is the value of pq?

View results